2020
DOI: 10.1016/j.jpsychores.2020.109970
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptom severity as a predictor of attendance in the HOME behavioral weight loss trial

Abstract: Highlights Higher baseline depressive symptom severity associated with poorer attendance  Cognitive-affective and somatic clusters both contributed to these associations  Greater baseline depressive symptoms may inhibit behavioral weight loss outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Second, mothers with higher depressive symptoms were more likely to be in the low attendance class, regardless of their initial score on the measure of home safety problems. This finding is consistent with several other studies that reported depressive symptoms in relation to intervention attendance [ 5 7 ]. Although the mechanism underlying the association between depressive symptoms and attendance is unknown, there are several possibilities.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Second, mothers with higher depressive symptoms were more likely to be in the low attendance class, regardless of their initial score on the measure of home safety problems. This finding is consistent with several other studies that reported depressive symptoms in relation to intervention attendance [ 5 7 ]. Although the mechanism underlying the association between depressive symptoms and attendance is unknown, there are several possibilities.…”
Section: Discussionsupporting
confidence: 93%
“…Few studies have used LCA to assess intervention attendance. The traditional analytic approach to attendance depends on the number of sessions attended, treating all sessions in a similar manner with no differentiation, and arbitrarily defining a cutoff for the number of sessions [ 7 ]. LCA is a person-centered, model-based approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression before bariatric surgery is associated with less weight loss after bariatric surgery [22 ▪ ]. Adults with obesity and elevated depression symptoms were found to be less likely to attend behavioral weight-loss sessions, less likely to achieve at least 5% weight loss, and had lower overall mean weight loss [23]. Ongoing assessment of depression after surgery is important.…”
Section: Psychosocial Perspectivementioning
confidence: 99%
“…As many as two thirds of youth pursuing surgical weight loss reported preexisting mental health concerns (Björk et al, 2020). Child psychological concerns (e.g., poor attendance and difficulties adhering to the treatment regimen) have been associated with barriers to obesity treatment completion, supporting the need to assess psychological concerns for patients referred for pediatric obesity treatment (Raatz & Gross, 2021; Shell et al, 2020).…”
mentioning
confidence: 99%